DESIGN OF HACCP PLAN FOR HOME MADE SOYA MILK âVITADELINâ IN YOGYAKARTA - , NOERSATYO; , Dr. Jumeri, STP., M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Soya milk production in Indonesia mostly comes from a small scale homebased or small mill industry. Rarely home-based industry had implemented their quality control system to produce quality and safe product. Nowadays, demand for guaranteed quality and food safety from international consumer and even local has increased gradually. On the other hand, food contamination from microorganism and poisonous materials remains a serious problem for most of the developing country, including Indonesia. The objectives of this study was to analyze specific home made soya milk and comparing it to the Indonesia National Standard for product qualification and to establish a specific HACCP plan to help the home-based industry produce quality and safer product. Analyzing the product was done based on Indonesian National Standard for soya milk (SNI 01-3830-1995). Sample of the product was taken to the laboratory for microbiological, and chemical testing. The design of HACCP plan was made specifically for Vitadelin soya milk home-based industry located in Jombor Baru which need a better quality control system to produce quality and safer soya milk. The HACCP model was developed based on the seven principles of HACCP. The prerequisite program contributes as a supporting system to deal with some hazards as a preventive action. The product description was used to alert the consumer to the potential hazards in the final products. Then, the potential control points of the hazards appeared in both raw material and the process will be studied along with the prevention actions. By answering the questions in the decision trees, the critical control points were identified. Finally, the HACCP control chart was developed. The result showed that Vitadelin soya milk was not qualified for Indonesian National Standard for soya milk. The HACCP model was developed based on the seven principles of HACCP to help fulfilling the standard requirement. There were 5 process steps classified as critical control point and 3 steps were needed to be modified. The HACCP plan was recommend to be implemented to this home-based industry in order to produce safer and quality soya milk.